The Effects of Coronavirus on Global Relations and Strategy Making in International Arena - Peshawa Mohammed Ali (Eurasian Journal of Management & Social Sciences, 2020)
This research explores the effects of coronavirus on global relations and strategy making in the international arena. Coronavirus or Covid-19 is a newly discovered virus in the world examined dynamically at the existing world. The indisposition of the virus might retain up enhancing the opinion of the spread of the contagion rate and the absence of a suitable vaccine (Lipsitch, Swerdlow, & Finelli, 2020). Covid-19 was initially testified from Wuhan, China, and formerly on it directed to a dynamic spread leading it to convert as a worldwide pandemic which led to a consequential international situation which has obstructed many subdivisions Internationally, including Worldwide Policies, Systematic signs of progress, Financial Effects over the several nations and worldwide relations between the countries. Thus, this paper tries to determine the potential effects and consequences of the Covid-19 pandemic over the global level and few conceivable ways to be controlled efficiently.